Serendipity and inherent non-linear thinking can help address the climate and environmental conundrums - Quan-Hoang Vuong; Viet-Phuong La; Minh-Hoang Nguyen (Sustainability: Science, Practice, & Policy)
Humankind is currently confronted with a critical challenge that determines its very existence, not only on an individual, racial, or national level but as a whole species: the fight against climate change and environmental degradation. To win this battle, humanity needs innovations and non-linear thinking. Nature has long been a substantial information source for unthinkable discoveries that save human lives. This Commentary suggests that by understanding the nature, emergence, and mechanism of serendipity, the survival skill of humans, humanity can capitalize on it to learn from nature and generate nature-based innovations that can address the climate and environmental degradation crises. Building an eco-surplus culture that incorporates core values pertaining to nature and sees environmental sustainability as the conscience of the times is essential to direct and leverage the power of serendipity in climate and sustainability science. In the era of artificial intelligence (AI) proliferation, AI will be a vital tool that provides navigational and useful information that aids the encounters and attainments of serendipity. However, given the tremendous power of AI, especially when combined with humans’ serendipity capability, its development and use must be approached with caution and ethical considerations to avoid adverse effects on environmental sustainability. Investment in other scientific areas beyond environmental research is also crucial, as it expands humanity’s knowledge base – an essential foundation for serendipitous discoveries through inter- and transdisciplinary interactions.